A method for modifying a superabsorbent aggregate

CN122916490APending Publication Date: 2026-10-16SHANDONG SHITONG HIGHWAY CONSTR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611368459.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]针对现有技术中高吸水率骨料改性效果差、无法利用孔隙优势、骨料与水泥水化产物粘接性能不足等问题,本发明提供了一种高吸水率骨料的改性方法,首先在微膨胀高粘性渗透材料中额外加入磁铁颗粒,待其渗透至骨料孔隙后,将骨料浸泡到含有磁流体的中空PVA纤维的碱性溶液中,在碱性作用下,高粘性材料凝胶硬化并发生微膨胀,将纤维管死死钉在孔隙内硬化的填充物内,同时纤维管另一端延伸至骨料外表面形成稳定连接;其中,中空PVA纤维管中磁流体采用“提前抽真空、再填充”的方式制备,确保磁流体填充饱满,将高粘性材料与纤维材料分开加入

Benefits of technology

(1)本发明打破传统改性思路,不将高吸水率骨料的孔隙视为性能劣化特征,反而将其作为微膨胀高粘性渗透材料的渗透空间,通过“高粘性材料与纤维材料分开加入”的设计,结合磁铁颗粒与磁流体的磁性协同作用,彻底解决“纤维一侧端部进入孔隙内部、另一侧端部向外延伸”的技术难题,实现纤维管“内锚牢固、外伸稳定”的精准效果,从根本上提升骨料与水泥浆体的力学桥接性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a modified method of high water absorption aggregate. The modified method comprises the following steps in sequence: cleaning and drying pretreatment of the high water absorption aggregate; mixing alkali responsive micro-expansion high-viscosity matrix material, magnet particles, crystal nucleus material and anhydrous ethanol to form micro-expansion high-viscosity permeation material; putting the pretreated aggregate into the micro-expansion high-viscosity permeation material, and vacuum-pressurized impregnation to obtain high water absorption aggregate containing the permeation material; uniformly dispersing the fiber tube filled with magnetic fluid in the alkali dispersion liquid to form a fiber tube dispersion liquid; putting the high water absorption aggregate containing the permeation material into the fiber tube dispersion liquid, soaking, taking out and curing to obtain modified high water absorption aggregate. Through the design, the technical pain point that the one side end of the fiber enters the inside of the pore and the other side end extends outward is solved, the adhesion with the cement hydration product is strengthened in combination with the synergistic effect of the crystal nucleus material, and the mechanical property and the durability of the concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete aggregate modification technology, specifically relating to a method for modifying aggregates with high water absorption. Background Technology

[0002] In concrete preparation, aggregates are a major component, and their properties directly affect the strength, durability, and workability of concrete. High-absorption aggregates, due to their wide availability and low cost, have certain application potential in engineering. However, the presence of numerous interconnected or closed pores within them results in lower strength, higher water absorption, and poor interfacial adhesion with cement paste, becoming a key bottleneck restricting their large-scale application. Current technologies for modifying high-absorption aggregates primarily focus on surface sealing treatments, such as coating the aggregate surface with cement paste or resin, attempting to prevent water penetration and improve surface strength. However, these methods only cover the aggregate surface and cannot penetrate into the internal pores, failing to fundamentally solve the performance degradation problem caused by the internal porosity of the aggregate. Furthermore, the surface coating does not bond tightly to the aggregate interior and is prone to detachment during concrete mixing and molding, resulting in limited modification effects. Meanwhile, existing modified materials often focus only on improving the adhesion between the aggregate surface and the cement paste, neglecting the utilization of the aggregate's internal pores, thus failing to achieve a technological breakthrough that "turns disadvantages into advantages." Furthermore, some modified materials have poor compatibility with cement hydration products, failing to form a stable bonding interface, and lack the micro-expansion characteristics in the alkaline environment of concrete. They cannot tightly anchor themselves to the aggregate pores like expansion bolts, instead resulting in uneven shrinkage, reducing the adhesion between different solid phases, and making it difficult to effectively improve the overall performance of concrete. Therefore, developing a method that can penetrate the aggregate interior, fully utilize the pore structure, possess alkaline-responsive micro-expansion characteristics, and precisely modify adhesion performance has become a pressing technical problem to be solved in this field. Summary of the Invention

[0003] To address the problems of poor modification effect of high water absorption aggregates, inability to utilize porosity advantages, and insufficient adhesion between aggregates and cement hydration products in existing technologies, this invention provides a method for modifying high water absorption aggregates. First, magnetic particles are added to a micro-expanding, high-viscosity, permeable material. After the magnetic particles penetrate into the aggregate pores, the aggregate is immersed in an alkaline solution containing magnetic fluid in hollow PVA fibers. Under alkaline conditions, the high-viscosity material gels, hardens, and undergoes micro-expansion, firmly anchoring the fiber tubes within the hardened filler in the pores. Simultaneously, the other end of the fiber tube extends to the outer surface of the aggregate, forming a stable connection. The magnetic fluid in the hollow PVA fiber tubes is prepared using a "pre-vacuuming and then filling" method to ensure full filling, with the high-viscosity material and fiber material added separately. This invention, through this design, achieves "one end of the fiber entering the pores while the other end extends outwards," combined with the synergistic effect of nucleation materials, strengthening the adhesion with cement hydration products, thereby significantly improving the mechanical properties and durability of concrete.

[0004] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A method for modifying aggregates with high water absorption includes the following steps: (1) Aggregate pretreatment: Select high water absorption aggregate, wash with water to remove surface impurities, dust, etc., put it into a drying equipment, dry it to constant weight at 80~120℃, and then cool it to room temperature for use. The high water absorption aggregate is natural aggregate, recycled aggregate, ceramsite, volcanic rock or pumice with a water absorption rate of 5% or higher; (2) Preparation of micro-expansion high viscosity permeable material: mix alkaline responsive micro-expansion high viscosity matrix material, magnetic particles, crystal nucleus material and anhydrous ethanol, put them into a closed stirrer and stir until a uniform, precipitate-free emulsion micro-expansion high viscosity permeable material is formed; In this step, the stirring speed is 180~300 r / min, and the stirring time is 20~40 min. The stirring process is closed to prevent ethanol evaporation. The role of the magnetic particles is to enhance the adsorption force between the permeation material and the subsequent hollow PVA fiber tube, assist in the positioning of the fiber tube, and ensure that the end of the fiber tube is accurately embedded into the pores. In this step, the high viscosity matrix material, magnetic particles, crystal nucleation materials and ethanol are mixed to form an emulsion-alkaline responsive micro-expansion high viscosity matrix material. This material can both inhibit the reaction by anhydrous ethanol and make it flowable to achieve good filling. It can also allow the ethanol to evaporate and flow out of the pores in the later stage, providing a channel for subsequent water to penetrate in, so that the viscous material can expand and hydrate. The mass fractions of the above raw materials are as follows: 60-80 parts of alkaline-responsive micro-expansion high-viscosity matrix material 1-3 parts magnet particles 2-8 parts of crystal nucleus material, 20-25 parts of anhydrous ethanol; (3) First stage of infiltration: The high water absorption aggregate after the pretreatment in step (1) is placed into the micro-expansion high viscosity infiltration material prepared in step (2), and the aggregate is impregnated by vacuum pressure impregnation method to achieve full infiltration of the infiltration material, laying the foundation for the "inner anchor and outer extension" of the fiber tube; after impregnation, the high water absorption aggregate containing the infiltration material is taken out and naturally dried at room temperature of 20~30℃ for later use; (4) Preparation of magnetic fluid-filled hollow PVA fiber tube: First, place the hollow PVA fiber tube into a vacuum device and evacuate it to -0.07~-0.10MPa, and maintain it for 15~25min; then slowly inject the magnetic fluid into the vacuum device of the hollow PVA fiber tube under vacuum. After filling, let it stand for 10~20min to ensure that the magnetic fluid is uniformly filled inside the PVA fiber tube, further improving the magnetic and mechanical properties of the fiber tube, and obtaining the magnetic fluid-filled fiber tube. (5) Second stage fiber tube anchoring: The magnetic fluid-filled fiber tube prepared in step (4) is uniformly dispersed in an alkaline dispersion to form a fiber tube dispersion; the high water absorption aggregate containing permeable material obtained after step (3) is placed in the fiber tube dispersion and soaked for 20~40 min, during which the solution temperature is maintained at 25~35℃. With the help of the magnetic adsorption effect of the magnetic particles and the magnetic fluid, one end of the hollow PVA fiber tube is precisely embedded in the permeable material in the pores inside the aggregate, and the other end naturally extends to the outer surface of the aggregate; at the same time, the alkaline dispersion triggers the micro-expansion high viscosity permeable material in the pores to gel harden. The hardened and expanded permeable material nails the embedded end of the fiber tube firmly into the pores, forming a firm "expansion anchoring-magnetic adsorption" double fixing structure. The extended end of the fiber tube is exposed on the surface of the aggregate, providing a connection point for subsequent bonding with cement paste; (6) Surface forming and curing: Take out the aggregate after step (5), rinse off the excess fiber tube dispersion liquid on the surface, put it in the curing box, and cure it for 12-24 hours at a temperature of 20~25℃ and a relative humidity of 60%~80% to make the permeable material in the pores completely harden and the bond between the fiber tube and the permeable material more firm. At the same time, a continuous and dense protective layer (composed of hardened permeable material and exposed fiber tube ends) is formed on the surface of the aggregate, thereby obtaining modified high water absorption aggregate. After the modified high water absorption aggregate is added to the concrete, the hardened permeable material inside reacts further with the alkaline environment of the concrete. The magnetic fluid inside the fiber tube and the concrete hydration products work together to further strengthen the bond between the fiber tube and the cement paste and improve the overall mechanical properties.

[0005] Furthermore, the high water absorption aggregate mentioned in step (1) has a particle size of 5~31.5mm and a moisture content of ≤0.1% after drying. This avoids the internal moisture of the aggregate from affecting the penetration and curing effect of the penetrating material. At the same time, it avoids the premature reaction between the moisture and the micro-expansion components and magnetic particles, ensuring that the micro-expansion effect and magnetic adsorption are precisely triggered in the second stage, thus guaranteeing the forming effect of "double anchoring" and "inner anchor and outer extension" of the fiber tube.

[0006] Further, the alkaline-responsive micro-expansion high-viscosity matrix material mentioned in step (2) is prepared by adding a mixture of micro / nano montmorillonite (particle size 10nm~20μm), micro / nano sodium silicate particles (particle size 10nm~20μm) with a modulus not higher than 1.5, and nano-silica (particle size 10~200nm) in a mass ratio of 10:1~2:0.5~1 to anhydrous ethanol, with the mass ratio of anhydrous ethanol to the mixture being 1~2:1; this matrix material can undergo water absorption and micro-expansion in an alkaline environment (pH=13~14) and... The reaction generates micro-expansion hydration products, which can not only fully fill the internal pores of the aggregate, but also form a stable bond with the aggregate surface and cement hydration products, thus achieving "expansion bolt" type anchoring. The specified particle size ensures that it can penetrate into the aggregate pores. After montmorillonite, sodium silicate, and nano silica penetrate into the coarse aggregate in this ratio, the alkali solution penetrates in during the subsequent soaking in the fiber tube suspension. The expansion of montmorillonite, the dissolution and viscosity of sodium silicate, and the reaction of nano silicate with alkaline sodium silicate increase the modulus and viscosity, thereby improving the fixation effect on the fibers.

[0007] In step (2), the alkaline-responsive micro-expansion high-viscosity matrix material, when used in low amounts, has insufficient expansion, making it unable to form a tight bond with the aggregate pore walls or firmly anchor the fiber tube embedded ends, resulting in poor anchoring effect (e.g., when the dosage is low, the fiber tube embedded ends are prone to loosening, and the interface bonding strength improvement is limited); when the dosage is high, excessive expansion will generate excessive internal stress, causing the aggregate pore walls to crack, which in turn reduces the strength of the aggregate itself (e.g., if the dosage ratio is too high, the splitting tensile strength of the aggregate decreases); therefore, controlling the dosage of micro-expansion material can ensure the "expansion bolt" type anchoring effect and avoid aggregate cracking, combining practicality and scientificity, while providing a stable carrier for fixing the fiber tube embedded ends.

[0008] Further, the nucleus material mentioned in step (2) is obtained by mixing nano-hydroxyapatite nuclei and nano-CSH at a mass ratio of 2 to 1:1, and its dosage is 3% to 10% of the mass of the alkaline-responsive micro-expansion high-viscosity matrix material; the size of the nano-hydroxyapatite nuclei and nano-CSH is controlled at 10 to 200 nm; the hydroxyl groups on the surface of the nucleus material of the present invention can react with Ca in the cement hydration products. 2+ Si 4+Chemical reactions occur, which serve as nucleation sites for cement hydration products, lowering the nucleation energy barrier of hydration products, promoting the generation and growth of hydration products such as CSH gel, and strengthening the bonding effect between modifiers and cement hydration products. Compared with single admixture, proportional mutual admixture can more fully exert the early strength and strengthening effect.

[0009] Furthermore, the magnetic particles mentioned in step (2) have a particle size of 50nm~100μm and a purity of ≥98%. This particle size can be uniformly dispersed in the permeation material and can generate stable magnetic adsorption with the magnetic fluid. When the dosage is 1~3 parts, the magnetic adsorption force is moderate and can accurately guide the fiber tube to be positioned. When the dosage is <1 part, the magnetic adsorption force is insufficient and cannot accurately guide the hollow PVA fiber tube to be positioned, and the fiber tube is prone to deviation. When the dosage is >3 parts, the dosage is too high and will affect the fluidity and permeation effect of the permeation material, and will lead to a weakening of the adhesion after the permeation material hardens. This dosage range can take into account the magnetic adsorption effect, the fluidity and mechanical properties of the permeation material, and form the best magnetic synergy with the magnetic fluid filling the hollow PVA fiber tube, ensuring the accuracy of the fiber tube's "inner anchor and outer extension".

[0010] Further, the specific process of the vacuum impregnation method in step (3) is as follows: first, the pretreated high water absorption aggregate is vacuumed, and then the high water absorption aggregate is impregnated under pressure so that the penetrating material can fully penetrate into the internal pores of the aggregate; the vacuum degree of the vacuum pressure impregnation method is -0.06~-0.09MPa, the pressure is 0.3~0.8MPa, and the impregnation time is 30~90min. The internal air can be discharged by vacuum pressure to ensure that the subsequent magnetic fluid is fully filled; furthermore, during the vacuum pressure impregnation process, the penetrating material is stirred once every 15~20min (stirring speed 60~300r / min, stirring time 2~3min) to ensure that the concentration of the penetrating material is uniform, to avoid the local decrease in the concentration of the penetrating material due to aggregate adsorption, which affects the penetration effect, the uniform distribution of magnetic particles and the uniformity of subsequent micro-expansion, and to prevent local excessive expansion from causing aggregate cracking and local insufficient expansion from affecting the anchoring effect.

[0011] Furthermore, the hollow PVA fiber tube mentioned in step (4) has a diameter of 0.05~0.2mm and a length of 2~5mm; its length is adapted to the depth of aggregate pores and the extension requirements of aggregate surface, ensuring that one end can be embedded in the pores and the other end can extend to the outer surface of the aggregate; a diameter > 0.2mm cannot penetrate small pores, a diameter < 0.05mm has insufficient mechanical strength and is prone to breakage; a length < 2mm cannot be exposed, a length > 5mm is prone to entanglement and interface strength reduction; if the length is too short, "inner anchor and outer extension" cannot be achieved (insufficient length of the embedded end and the outer extension end cannot be exposed), and if the length is too long, it will affect the bonding performance; when selecting the PVA fiber tube, its specific diameter should be determined according to the pore size of the aggregate surface, and the diameter of the hollow PVA fiber tube should not be greater than 2 / 3 of the pore size D50 of the aggregate surface, ensuring that one end can penetrate into the pores and the other end can extend to the outer surface of the aggregate, so as to achieve stable mechanical bridging.

[0012] Further, the magnetic fluid mentioned in step (4) is a mixture of nano-magnetic particles and alkaline dispersion. The mass percentage of nano-magnetic particles in the magnetic fluid is 5% to 10%. If the content is too low, the magnetic response will be insufficient. If the content is too high, the magnetic fluid will have poor fluidity and will not be able to fill the fiber tube. The particle size of the nano-magnetic particles is 5 to 20 nm. Furthermore, the alkaline dispersion in steps (4) and (5) is prepared by sodium hydroxide and deionized water, with a pH value of 13-14, providing alkaline triggering conditions for the subsequent gel hardening of the permeation material. In step (5), the pH value of the alkaline dispersion is 13-14. If the pH value is too low, the gel hardening and micro-expansion of the permeation material cannot be triggered. If the pH value is too high, the hardening speed of the permeation material will be too fast, generating internal stress. The soaking temperature is 25-35℃, and the soaking time is 20-40min. If the soaking temperature is too low, the reaction rate will be slow. If the soaking time is insufficient, the fiber tube will not be accurately positioned and the permeation material will not harden sufficiently. If the soaking time is too long, the process cost will increase. This parameter range has been verified by multiple sets of experiments, which can ensure that the permeation material is fully hardened, the micro-expansion effect is stable, and the fiber tube accurately achieves "internal anchor and external extension".

[0013] Furthermore, in the modification method of the present invention, when determining the particle size of magnetic particles, fiber tube diameter, magnetic fluid nanoscale magnetic particles, crystal nucleus materials, and alkaline responsive micro-expansion high viscosity matrix materials, the pore size of the aggregate should be considered in advance to ensure that the particles can penetrate into the pores.

[0014] The core innovation of this invention lies not only in transforming aggregate porosity from a disadvantage to an advantage, achieving dual fixation through "micro-expansion anchoring + fiber reinforcement," but also in constructing a three-level synergistic reinforcement system of "internal dual anchoring - interfacial chemical induction - external fiber bridging" by using a design that "separately adds high-viscosity materials and fiber materials" combined with the fabrication process of magnetic fluid-filled hollow PVA fiber tubes. This system achieves "one end of the fiber enters the pores while the other end extends outwards." The components and processes are not simply superimposed but undergo complex physicochemical synergistic effects at different scales and stages. The specific mechanism is as follows: (1) Internal dual anchoring effect: The micro-expansion high viscosity permeable material permeates into the internal pores of the aggregate under vacuum / pressurization conditions. The added magnetic particles are uniformly dispersed in the permeable material, providing magnetic adsorption sites for the subsequent positioning of hollow PVA fiber tubes. When the aggregate is immersed in an alkaline solution of fiber tubes filled with magnetic fluid, the alkaline environment triggers the permeable material to undergo gel micro-expansion hardening. The hardened permeable material after expansion is like an "expansion bolt" tightly biting into the pore wall of the aggregate. At the same time, the magnetic particles and the magnetic fluid inside the fiber tube generate magnetic adsorption, guiding one end of the fiber tube to be precisely embedded in the permeable material in the pores. The hardened permeable material firmly nails the embedded end of the fiber tube, forming a dual fixing structure of "micro-expansion anchoring + fiber reinforcement". This solves the problem that traditional fibers cannot achieve firm bonding inside the pores, achieving high-strength anchoring from inside the aggregate, providing a solid foundation for subsequent external fiber bridging, while filling the pores and improving the density of the aggregate itself. In this process, after mixing with anhydrous ethanol, the penetrating material will slowly evaporate after it has completely penetrated into the aggregate voids. This reduces the lubricity between the aggregate and the penetrating material, increases the friction between particles, and allows the material to remain completely within the aggregate. It also leaves voids after the ethanol evaporates. These voids provide space for the penetration of alkaline solution and the generation of swelling hydration products in the later stages.

[0015] (2) Interface-induced effect (catalytic effect of crystal nuclei): The bonding between traditional modifiers and cement hydration products is mostly physical bonding with low strength. In this invention, the nanocrystal nuclei pre-incorporated into the permeable material act as heterogeneous nucleation sites in the early stage of cement hydration: the nanocrystal nuclei have a similar crystal structure to the CSH gel generated by cement hydration, which can induce cement hydration products to grow directionally and interweave tightly on the surface of the permeable material and the hollow fiber tube, thereby increasing the interfacial bonding strength by an order of magnitude. This, together with the internal double anchoring structure and the external fiber bridging, further strengthens the bond between aggregate and cement paste.

[0016] (3) External fiber bridging effect (magnetic fluid filled fiber tube, accurately realizing "internal anchor and external extension"): This invention achieves the technical feature of "one end of the fiber enters the pore and the other end extends outward" by designing "high viscosity material and fiber material are added separately" and combining the vacuum preparation process of magnetic fluid filled fiber tube. Compared with the traditional solid fiber incorporation method, it avoids the problems of "difficult penetration and uneven extension" and achieves the precise effect of "firm internal anchor and stable external extension". It works synergistically with internal double anchoring and interface chemical induction to make the bonding interface have "strong and tough" mechanical properties, further improving the overall stability.

[0017] In summary, the synergistic effect of the four components is as follows: the micro-expansion high-viscosity permeable material provides the physical framework and achieves micro-expansion anchoring; the magnetic particles and magnetic fluid work together to achieve precise positioning of the fiber tube; the crystal nucleus material provides chemical bonding; and the fiber tube provides external mechanical bridging. This system is indispensable. Without the magnetic particles, the fiber tube cannot be precisely positioned and embedded in the pores; without the magnetic fluid filling, the fiber tube lacks magnetic response capability and its own strength is insufficient; without the crystal nucleus, it cannot form a chemical bond with the cement stone; and without the micro-expansion properties, the permeable material cannot form a tight anchor with the aggregate pores, and the embedded end of the fiber tube is prone to loosening.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention breaks with the traditional modification approach. Instead of regarding the pores of high water absorption aggregate as a performance degradation feature, it uses them as the permeation space of micro-expansion high viscosity permeable material. By designing the "separate addition of high viscosity material and fiber material", combined with the magnetic synergistic effect of magnetic particles and magnetic fluid, the technical problem of "one end of fiber entering the pore and the other end extending outward" is completely solved, achieving the precise effect of "firm internal anchoring and stable external extension" of fiber tube, fundamentally improving the mechanical bridging performance of aggregate and cement paste.

[0019] (2) Innovative construction of a dual fixing structure of “micro-expansion anchoring + magnetic adsorption”. The micro-expansion high-viscosity permeable material hardens and expands in an alkaline environment, firmly nailing the fiber tube embedded end into the pore. The magnetic particles and magnetic fluid work together to achieve precise positioning of the fiber tube, avoiding fiber tube displacement and loosening. Compared with the traditional single anchoring method, the anchoring strength is improved, solving the problem of loose bonding and easy detachment between the traditional fiber and the aggregate, and turning the aggregate porosity disadvantage into the anchoring advantage.

[0020] (3) The present invention innovatively improves the bonding performance of aggregate paste interface by synergistic application of materials such as micro-expansion high viscosity material, nano hydroxyapatite crystal nuclei, magnetic particles, and magnetic fluid-filled hollow PVA fiber tubes. Compared with traditional modified materials, it significantly improves the bonding performance of aggregate paste interface and enhances the durability and mechanical properties of concrete. It can form a strong bonding layer with the aggregate surface and achieve tight fixation inside the pores by relying on double anchoring. It can also form a stable mechanical bridge with cement hydration products through the extended end of the fiber tube, thereby improving the comprehensive performance of concrete.

[0021] (4) The hollow fiber tube adopts the process of "pre-vacuuming and then filling with magnetic fluid" to ensure that the magnetic fluid is fully filled and without gaps. This not only improves the magnetic response capability of the fiber tube, but also enhances the mechanical strength of the fiber tube itself. At the same time, the magnetic fluid and the concrete hydration products work together to further strengthen the bond between the fiber tube and the cement paste, thereby improving the overall mechanical properties of the concrete.

[0022] (5) The modification method of the present invention has better performance than traditional materials. The modified aggregate has stable performance and can be directly used for concrete preparation. It can significantly improve the performance of concrete, expand the application range of high water absorption aggregate, conform to the development trend of green building materials, and has good engineering application value and economic benefits. Detailed Implementation

[0023] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.

[0024] Example 1 A method for modifying aggregates with high water absorption includes the following steps: (1) Aggregate pretreatment: Select high water absorption aggregate, remove surface impurities, dust and loose particles, put it into a drying equipment, dry it to constant weight at 105℃, and cool it to room temperature for later use; the high water absorption aggregate is natural aggregate with a water absorption rate of 8.5%; (2) Preparation of micro-expansion high viscosity permeable material: According to the mass fraction, 68 parts of alkaline responsive micro-expansion high viscosity matrix material, 2 parts of magnetic particles, 6 parts of crystal nucleation material and 22 parts of anhydrous ethanol are mixed and placed in a stirrer. The mixture is stirred at 200 r / min for 30 min to form a uniform, precipitate-free emulsion permeable material. The mixture is sealed during the stirring process to prevent ethanol evaporation. (3) First stage of infiltration: The pretreated high water absorption aggregate is placed into the micro-expansion high viscosity infiltration material prepared in step (2). The vacuum pressure impregnation method is used. First, the aggregate is vacuumed, and then the aggregate is impregnated under pressure so that the infiltration material can fully penetrate into the internal pores of the aggregate. The impregnation time is 60 min. The vacuum degree of the vacuum impregnation method is -0.08 MPa, and the pressure of the pressure impregnation method is 0.5 MPa. After the impregnation is completed, the aggregate is taken out, and the excess infiltration material on the surface is removed for later use. (4) Preparation of magnetic fluid-filled hollow PVA fiber tubes: First, the PVA fiber tubes are placed in a vacuum device and evacuated to -0.08MPa. The vacuum state is maintained for 20 minutes to ensure that there is no air or void inside the fiber tubes. Then, the magnetic fluid is slowly injected into the fiber tubes under vacuum. After filling, the tubes are left to stand for 15 minutes to ensure that the magnetic fluid is uniformly filled inside the fiber tubes without air bubbles or voids, thus obtaining magnetic fluid-filled fiber tubes. The fiber tubes have a diameter of 0.1mm and a length of 3mm. The length is adapted to the depth of aggregate pores and the extension requirements of aggregate surface, ensuring that one end can be embedded in the pores and the other end can extend to the outer surface of the aggregates. The magnetic fluid is a mixture of nano-magnetic particles and alkaline dispersion. The content of nano-magnetic particles is 8%, and the pH value of alkaline dispersion is 13.8. (5) Second stage fiber tube anchoring: Prepare sodium hydroxide solution (pH 13.8), and uniformly disperse the magnetic fluid filled fiber tube prepared above in the alkaline solution to form a fiber tube dispersion; put the aggregate treated in step (3) into the fiber tube dispersion and soak for 30 min, during which the solution temperature is kept at 30℃. With the help of the magnetic adsorption effect of the magnetic particles and the magnetic fluid, guide one end of the hollow PVA fiber tube to be precisely embedded in the permeable material in the pores inside the aggregate, and the other end naturally extends to the outer surface of the aggregate. (6) Surface forming and curing: Take out the aggregate after step (5), remove the excess fiber tube dispersion liquid on the surface, put it into the curing box, and cure it for 18 hours at a temperature of 22.5℃ and a relative humidity of 70% to obtain modified high water absorption aggregate.

[0025] Furthermore, the alkaline-responsive micro-expansion high-viscosity matrix material is prepared by mixing micro-nano montmorillonite (10nm~50nm), micro-nano sodium silicate particles with a modulus of 1 (particle size 10nm~50nm), and nano-silica (10~50nm) in a mass ratio of 10:1.5:0.6 and then adding them to anhydrous ethanol (the amount of which is in a mass ratio of 1.5:1 to the mixture).

[0026] Furthermore, the nucleus material is prepared by mixing nano-hydroxyapatite nuclei and nano-CSH at a mass ratio of 1.5:1; the size of the nano-nuclei is 50-80 nm, and the doping amount is 6% of the mass of the alkaline-responsive micro-expansion high-viscosity matrix material.

[0027] Furthermore, the magnet particles are 50nm-100nm in size and have a purity of 98%.

[0028] Furthermore, the hollow fiber tube is made of PVA, with a diameter of 0.1 mm and a length of 3 mm; the magnetic fluid contains nano-magnetic particles with a particle size of 5-20 nm and a content of 8%; the alkaline dispersion is prepared by sodium hydroxide and deionized water, with a pH value of 13.8.

[0029] Furthermore, in step (1), the high water absorption aggregate has a particle size of 5-31.5 mm in continuous gradation and a moisture content of 0 after drying.

[0030] Furthermore, in step (3), the impregnation material is stirred once every 18 minutes during the impregnation process (stirring speed 100 r / min, stirring time 2.5 min).

[0031] Furthermore, in step (5), the pH value of the alkaline solution is 13.8, the soaking temperature is 30℃, and the soaking time is 30min.

[0032] Example 2 A method for modifying aggregates with high water absorption includes the following steps: (1) Aggregate pretreatment: Select high water absorption aggregate, remove surface impurities, dust and loose particles, put it into a drying equipment, dry it to constant weight at 80℃, and cool it to room temperature for later use; the high water absorption aggregate is recycled coarse aggregate with a water absorption rate of 9.6%; (2) Preparation of micro-expansion high viscosity permeable material: According to the mass fraction, 60 parts of alkaline responsive micro-expansion high viscosity matrix material, 1 part of magnetic particles, 2 parts of crystal nucleation material and 20 parts of anhydrous ethanol are mixed and placed in a stirrer. The mixture is stirred at 180 r / min for 20 min to form a uniform, precipitate-free emulsion permeable material. The mixture is sealed during the stirring process to prevent ethanol evaporation. (3) First stage of infiltration: The pretreated high water absorption aggregate is placed into the micro-expansion high viscosity infiltration material prepared in step (2). The vacuum pressure impregnation method is used. First, the aggregate is vacuumed, and then the aggregate is impregnated under pressure so that the infiltration material can fully penetrate into the pores inside the aggregate. The impregnation time is 30 min. The vacuum degree of the vacuum impregnation method is -0.06 MPa, and the pressure of the pressure impregnation method is 0.3 MPa. After the impregnation is completed, the aggregate is taken out, and the excess infiltration material on the surface is removed for later use. (4) Preparation of magnetic fluid-filled hollow PVA fiber tube: First, the PVA fiber tube is placed in a vacuum device and evacuated to -0.07MPa. The vacuum state is maintained for 15 minutes. After filling, it is left to stand for 10 minutes to obtain the magnetic fluid-filled fiber tube. The diameter of the fiber tube is 0.05mm and the length is 2mm. The magnetic fluid is a mixture of nano-magnetic particles and alkaline dispersion. The content of nano-magnetic particles is 5%, and the pH value of alkaline dispersion is 13. (5) Second stage fiber tube anchoring: Prepare sodium hydroxide solution (pH 13), and uniformly disperse the magnetic fluid filled fiber tube prepared above in the alkaline solution to form a fiber tube dispersion; put the aggregate treated in step (3) into the fiber tube dispersion and soak for 20 min, during which the solution temperature is kept at 25℃; (6) Surface forming and curing: Take out the aggregate after step (5), remove the excess fiber tube dispersion liquid on the surface, put it into the curing box, and cure it for 12 hours at a temperature of 20℃ and a relative humidity of 60% to obtain modified aggregate.

[0033] Furthermore, the alkaline-responsive micro-expansion high-viscosity matrix material is prepared by mixing micro-nano montmorillonite (10nm~20nm), micro-nano sodium silicate particles with a modulus of 1.5 (10nm~20nm), and nano-silica (10~200nm) in a mass ratio of 10:1:0.5 and then adding it to anhydrous ethanol (the amount of which is in a mass ratio of 1:1 to the mixture).

[0034] Furthermore, the nucleus material is prepared by mixing nano-hydroxyapatite nuclei and nano-CSH in a mass ratio of 2:1; the size of the nano-nuclei is 50-80 nm, and the doping amount is 3% of the mass of the alkaline-responsive micro-expansion high-viscosity matrix material.

[0035] Furthermore, the magnet particles are 50nm-80nm in size, have a purity of ≥98%, and are added at 1% of the mass of the alkaline-responsive micro-expansion high-viscosity matrix material.

[0036] Furthermore, in step (1), the particle size of the high water absorption aggregate is 5~31.5mm, and the moisture content after drying is 0.

[0037] Furthermore, in step (3), the impregnation material is stirred every 15 minutes during the impregnation process (stirring speed 60 r / min, stirring time 3 min).

[0038] Example 3 A method for modifying aggregates with high water absorption includes the following steps: (1) Aggregate pretreatment: Select high water absorption aggregate, remove surface impurities, dust and loose particles, put it into a drying equipment, dry it to constant weight at 120℃, and cool it to room temperature for later use; the high water absorption aggregate is ceramsite with a water absorption rate of 15.3%; (2) Preparation of micro-expansion high viscosity permeable material: According to the mass fraction, 80 parts of alkaline responsive micro-expansion high viscosity matrix material, 3 parts of magnetic particles, 8 parts of crystal nucleus material and 25 parts of anhydrous ethanol are mixed and placed in a stirrer. The mixture is stirred at 300 r / min for 40 min to form a uniform, precipitate-free emulsion permeable material. The mixture is sealed during the stirring process to prevent ethanol evaporation. (3) First stage of infiltration: The pretreated high water absorption aggregate is placed into the micro-expansion high viscosity infiltration material prepared in step (2). The vacuum pressure impregnation method is used. First, the aggregate is vacuumed, and then the aggregate is impregnated under pressure so that the infiltration material can fully penetrate into the pores inside the aggregate. The impregnation time is 90 min. The vacuum degree of the vacuum impregnation method is -0.09 MPa, and the pressure of the pressure impregnation method is 0.8 MPa. After the impregnation is completed, the aggregate is taken out, and the excess infiltration material on the surface is removed for later use. (4) Preparation of magnetic fluid-filled hollow PVA fiber tube: First, the PVA fiber tube is placed in a vacuum device and evacuated to -0.10MPa, and the vacuum state is maintained for 25min; then, the magnetic fluid is slowly injected into the fiber tube under vacuum. After filling, it is left to stand for 20min to ensure that the magnetic fluid is uniformly filled inside the fiber tube, and a magnetic fluid-filled fiber tube is obtained; the fiber tube has a diameter of 0.2mm, a length of 5mm, a nano-magnetic particle content of 10%, and an alkaline dispersion pH of 14, which provides alkaline triggering conditions for subsequent gel hardening of the infiltrated material; (5) Second stage fiber tube anchoring: Prepare an alkaline solution (pH 14), and uniformly disperse the magnetic fluid-filled fiber tube prepared above in the alkaline solution to form a fiber tube dispersion; put the aggregate treated in step 3 into the fiber tube dispersion and soak for 40 minutes, during which the solution temperature is kept at 35°C. With the help of the magnetic adsorption effect of the magnetic particles and the magnetic fluid, guide one end of the hollow PVA fiber tube to be precisely embedded in the permeable material in the pores inside the aggregate, and the other end naturally extends to the outer surface of the aggregate. (6) Surface forming and curing: Take out the aggregate after step 5, remove the excess fiber tube dispersion liquid on the surface, put it into the curing box, and cure it for 24 hours at a temperature of 25℃ and a relative humidity of 80% to obtain modified aggregate.

[0039] Furthermore, the alkaline-responsive micro-expansion high-viscosity matrix material is prepared by mixing micro-nano montmorillonite (1μm~20μm), micro-nano low-modulus sodium silicate particles (50nm~20μm), and nano-silica (100~200nm) in a mass ratio of 10:2:1 and then adding it to anhydrous ethanol (the amount of which is in a mass ratio of 2:1 to the mixture).

[0040] Furthermore, the crystal nucleus material is prepared by mixing nano-hydroxyapatite crystal nuclei and nano-CSH in a 1:1 mass ratio; the size of the nano-crystal nuclei is 100-200 nm, and the doping amount is 10% of the mass of the alkaline-responsive micro-expansion high-viscosity matrix material.

[0041] Furthermore, the magnet particles are 50nm-100μm in size, 99% pure, and are added at 3% of the mass of the alkaline-responsive micro-expansion high-viscosity matrix material.

[0042] Furthermore, the hollow fiber tube is made of PVA, with a diameter of 0.2 mm and a length of 5 mm; the magnetic fluid contains 10% nano-magnetic particles with a particle size of 20 nm; and the alkaline dispersion is prepared from sodium hydroxide and deionized water with a pH value of 14.

[0043] Furthermore, in step (1), the particle size of the high water absorption aggregate is 5~31.5mm, and the moisture content after drying is 0.1%.

[0044] Furthermore, in step (3), the impregnation material is stirred once every 20 minutes during the impregnation process (stirring speed 300 r / min, stirring time 2 min).

[0045] Furthermore, in step (4), the vacuuming time of the hollow PVA fiber tube is 25 min, and the vacuum degree is -0.10 MPa; after filling with magnetic fluid, it is left to stand for 20 min to ensure that the magnetic fluid is evenly distributed inside the fiber tube.

[0046] Furthermore, in step (5), the pH value of the alkaline solution is 14, the soaking temperature is 35℃, and the soaking time is 40min.

[0047] Comparative Example 1 (Single material comparison, no magnetic components) The difference from Example 1 is that no magnetic particles are added to the alkaline-responsive high-viscosity micro-expansion component, while the other parameters are completely consistent with those of Example 1.

[0048] Comparative Example 2 (filled with non-magnetic fluid, the fiber tube is made of ordinary solid fiber, and the rest is the same as Example 1) The difference from Example 1 is that the fiber tube is replaced with ordinary PVA fiber, which is a solid structure and is not filled with magnetic fluid. All other materials and parameters are exactly the same.

[0049] Comparative Example 3 (High-viscosity material and fiber material were added simultaneously, and the rest was the same as in Example 1) To verify the necessity of adding "high-viscosity materials and fiber materials separately", Comparative Example 3 was set up: the same modification method as in Example 1 was used, the hollow PVA fiber tube and the impregnation material were mixed at the same time and impregnated at one time, without separating the two-stage treatment, and the other materials and parameters were completely the same.

[0050] Comparative Example 4 (no micro-expansion component, otherwise consistent with Example 1) To further verify the necessity of the micro-expansion component, a comparative example 4 was set up: the same modification method as in Example 1 was used to remove the micro-expansion component (micro-nano montmorillonite), while the remaining materials and parameters were completely identical.

[0051] Comparative Example 5 (for Example 1, without the addition of sodium silicate component) The same modification method as in Example 1 was used to remove sodium silicate, while the remaining materials and parameters were completely identical.

[0052] Comparative Example 6 (for Example 1, only an equal amount of CSH crystal nuclei were used for the nucleus-type component). Using the same modification method as in Example 1, only an equal amount of CSH crystal nuclei were used for the nucleus component, while the other materials and parameters were completely identical.

[0053] Comparative Example 7 (for Example 1, the fiber tube length is 1 mm) The length of the fiber tube was modified to 1 mm, and the rest was the same as in Example 1.

[0054] Comparative Example 8 (for Example 1, the fiber tube length is 7 mm) The fiber tube length was modified to 7mm, and the rest remained the same as in Example 1.

[0055] Concrete specimens were prepared using unmodified aggregates, prepared modified aggregates, and modified aggregates prepared in each comparative example to replace coarse aggregates (mix ratio: cement:coarse aggregate:sand:water = 1:3:2:0.5). (The cement was P.O42.5 cement, and the sand was natural medium sand with a fineness modulus of 2.7). The specimens were tested after curing for 28 days, and the results are shown in Table 1.

[0056] Table 1. Concrete properties of modified and unmodified aggregates applied in each example and comparative example. The results in Table 1 show that: In Example 1, the concrete prepared with modified aggregate showed a 44.7% increase in compressive strength, a 43.2% increase in flexural strength, and a 77.8% increase in splitting tensile strength compared to the unmodified aggregate concrete. This indicates that the use of modified aggregate improves the mechanical properties of the concrete and enhances the interfacial bonding between the aggregate and the paste (as indicated by splitting tensile strength).

[0057] In Example 2, the compressive strength of the concrete prepared with modified aggregate was increased by 38.1% compared with the concrete with unmodified aggregate; the flexural strength was increased by 29.5% compared with the concrete with unmodified aggregate; and the splitting tensile strength was increased by 66.7% compared with the concrete with unmodified aggregate. This indicates that the mechanical properties of concrete are improved after using modified aggregate, and the interfacial bonding performance between aggregate and paste is improved (characterized by splitting tensile strength).

[0058] In Example 3, the compressive strength of the concrete prepared with modified aggregate was increased by 60.1% compared with the concrete with unmodified aggregate; the flexural strength was increased by 46.2% compared with the concrete with unmodified aggregate; and the splitting tensile strength was increased by 138.9% compared with the concrete with unmodified aggregate. This indicates that the mechanical properties of concrete are improved after using modified aggregate, and the interfacial bonding performance between aggregate and paste is improved (characterized by splitting tensile strength).

[0059] The concrete prepared with modified aggregate in Comparative Example 1 showed a 4.7% decrease in compressive strength, a 14.3% decrease in flexural strength, and a 25% decrease in splitting tensile strength compared to the concrete prepared with modified aggregate in Example 1. This indicates that adding fibers alone, rather than using magnetic particles for precise orientation, does not significantly reduce the compressive strength of the concrete, but it does significantly reduce the flexural and splitting tensile strengths, especially the splitting tensile strength, which reflects interfacial bond strength. This suggests that the fiber tubes are misaligned, some cannot be embedded in the pores, some embedded ends are not securely fixed and are prone to loosening, and the exposed ends are unevenly distributed, resulting in poor mechanical bridging. The conclusion shows that the synergistic effect of the magnetic particles and the magnetic fluid is key to achieving precise positioning and secure internal anchoring of the fiber tubes. Without both magnetic particles and the magnetic fluid, the fiber tubes cannot be precisely embedded in the pores, the "internal anchoring and external extension" effect cannot be achieved, and the overall mechanical properties decrease significantly, proving that the synergistic effect of the magnetic particles is not obvious.

[0060] In Comparative Example 2, the compressive strength of the concrete prepared with modified aggregate decreased by 7.4% compared to the concrete prepared with modified aggregate in Example 1, the flexural strength decreased by 17.5%, and the splitting tensile strength decreased by 29.2%. This indicates that ordinary solid fibers cannot fully penetrate into the pores; most fibers only adhere to the aggregate surface, failing to achieve "internal anchoring and external extension." Consequently, the fibers easily detach under stress, resulting in poor crack resistance. This demonstrates that magnetic fluid filling can significantly improve the magnetic response, mechanical strength, and "internal anchoring and external extension" effect of fiber tubes. Ordinary solid fibers cannot solve the technical difficulties of "internal anchoring and external extension," proving the innovation and effectiveness of magnetic fluid-filled fiber tube technology.

[0061] In Comparative Example 3, the splitting tensile strength was only 62.5% of that in Example 1 of this invention, a decrease of 37.5%; the flexural strength of the concrete decreased by 25.4%; and the compressive strength decreased by 23.9% compared to Example 1. This indicates that directly mixing the high-viscosity particles with water without subsequent admixture severely affects the uniformity of penetration, leading to significant performance degradation in concrete. This is mainly because the high-viscosity particles dissolve in water to form a high-viscosity liquid, making penetration difficult. Furthermore, the fibers hinder liquid penetration, resulting in weak adhesion and uneven distribution and agglomeration of the fiber tubes. This demonstrates that the design of "separately adding high-viscosity materials and fiber materials" is a key process for achieving the "internal anchor and external extension" of the fiber tubes. Simultaneous addition would prevent the fiber tubes from being positioned or exposed, proving the non-obviousness of this process design.

[0062] In Comparative Example 4, the splitting tensile strength was only 79.2% of that in Example 1 of this invention; the concrete compressive strength was only 88.7% of that in Example 1 of this invention, and the flexural strength decreased by 17.5% compared to Example 1. This indicates that the micro-expansion component plays a crucial role in fixing, achieving "expansion bolt"-type anchoring and securing the embedded end of the fiber tube. Without the micro-expansion component, it is impossible to firmly nail the fiber tube inside the pores, nor can it fill the pores or improve the aggregate density, further proving the effectiveness of the "micro-expansion anchoring + magnetic adsorption" dual fixing structure of this invention.

[0063] In Comparative Example 5, the splitting tensile strength was only 83.3% of that in Example 1, a decrease of 16.7% compared to Example 1; the concrete compressive strength was only 91.1% of that in Example 1 of this invention, a decrease of 8.9%; and the flexural strength was 85.7% of that in Example 1, a decrease of 14.3% compared to Example 1. This is because sodium silicate dissolved in water can effectively act as a thickener, improving the adhesion between the filler material and the pore walls of the coarse aggregate, and enhancing the adhesion with fibers, thereby improving the overall adhesion performance.

[0064] In Comparative Example 6, the splitting tensile strength decreased by 8.3% compared to Example 1; the concrete compressive strength decreased by 6.8%, and the flexural strength decreased by 11.1% compared to Example 1. This demonstrates the effectiveness of the two nucleation-type components being blended, which, compared to a single component CSH, can improve the mechanical and adhesive properties.

[0065] In Comparative Example 7, the splitting tensile strength of the concrete was 3.4 MPa, the flexural strength was 5.2 MPa, and the compressive strength was 48.7 MPa. This indicates that a shorter fiber tube length leads to insufficient bonding between the aggregate and the paste, resulting in a decrease in strength.

[0066] In Comparative Example 8, the concrete exhibited a splitting tensile strength of 3.9 MPa, a flexural strength of 4.8 MPa, and a compressive strength of 50.2 MPa. This indicates that excessively long fiber tubes weaken the bond strength between aggregates and paste in the concrete, leading to decreased flexural and compressive strength. This is because excessively long fibers can cause entanglement and adhesion on the aggregate surface, creating defects between the paste and aggregate, thus negatively impacting the interfacial bonding.

Claims

1. A method for modifying high water absorption aggregate, characterized in that, Includes the following steps: (1) Aggregate pretreatment: Select high water absorption aggregate, wash with water to remove surface impurities, dust, etc., put it into a drying equipment, dry it to constant weight at 80~120℃, and then cool it to room temperature for use. (2) Preparation of micro-expansion high viscosity permeable material: mix alkaline responsive micro-expansion high viscosity matrix material, magnetic particles, crystal nucleus material and anhydrous ethanol, put them into a closed stirrer and stir until a uniform, precipitate-free emulsion micro-expansion high viscosity permeable material is formed; The mass fractions of the above raw materials are as follows: 60-80 parts of alkaline-responsive micro-expansion high-viscosity matrix material 1-3 parts magnet particles 2-8 parts of crystal nucleus material, 20-25 parts of anhydrous ethanol; (3) First stage of infiltration: The high water absorption aggregate after the pretreatment in step (1) is placed into the micro-expansion high viscosity infiltration material prepared in step (2), and the aggregate is impregnated by vacuum pressure impregnation method. After impregnation, the high water absorption aggregate containing the infiltration material is taken out and air-dried at room temperature of 20~30℃ for later use. (4) Preparation of magnetic fluid-filled hollow PVA fiber tube: First, put the hollow PVA fiber tube into a vacuum device and evacuate it to -0.07~-0.10MPa, and keep it for 15~25min; then slowly inject the magnetic fluid into the vacuum device of the hollow PVA fiber tube under vacuum. After filling, let it stand for 10~20min to obtain the magnetic fluid-filled fiber tube. The magnetic fluid is a mixture of nano-magnetic particles and an alkaline dispersion. (5) Second stage fiber tube anchoring: The magnetic fluid filled fiber tube prepared in step (4) is uniformly dispersed in an alkaline dispersion to form a fiber tube dispersion; the high water absorption aggregate containing permeable material obtained after step (3) is placed in the fiber tube dispersion and soaked for 20~40 min, during which the solution temperature is maintained at 25~35℃. (6) Surface forming and curing: Take out the aggregate after step (5), rinse off the excess fiber tube dispersion liquid on the surface, put it in the curing box, and cure it for 12-24 hours at a temperature of 20-25℃ and a relative humidity of 60%-80% to obtain modified high water absorption aggregate.

2. The method for modifying high water absorption aggregate according to claim 1, characterized in that, The high water absorption aggregate mentioned in step (1) is natural aggregate, recycled aggregate, ceramsite, volcanic rock or pumice with a water absorption rate of more than 5%; The high water absorption aggregate mentioned in step (1) has a particle size of 5~31.5mm and a moisture content of ≤0.1% after drying.

3. The method for modifying high water absorption aggregate according to claim 1, characterized in that, In step (2), the stirring speed is 180~300 r / min and the stirring time is 20~40 min.

4. The method for modifying high water absorption aggregate according to claim 1, characterized in that, The alkaline-responsive micro-expansion high-viscosity matrix material mentioned in step (2) is prepared by adding a mixture of micro-nano montmorillonite, sodium silicate particles and nano silica in a mass ratio of 10:1~2:0.5~1 to anhydrous ethanol. The mass ratio of anhydrous ethanol to the mixture is 1~2:

1. The nucleus material is obtained by mixing nano-hydroxyapatite nuclei and nano-CSH at a mass ratio of 2 to 1:1, and its dosage is 3% to 10% of the mass of the alkaline-responsive micro-expansion high-viscosity matrix material.

5. The method for modifying high water absorption aggregate according to claim 4, characterized in that, The micro / nano montmorillonite particles have a diameter of 10 nm to 20 μm; The sodium silicate particles are micro- and nano-sized, with a modulus not exceeding 1.5 and a particle size of 10 nm to 20 μm. The nano-silica particles have a diameter of 10~200nm.

6. The size of the nano-hydroxyapatite nuclei and nano-CSH is controlled within 10~200 nm; The magnet particles have a particle size of 50nm~100μm and a purity of ≥98%.

7. The method for modifying high water absorption aggregate according to claim 1, characterized in that, The specific process of the vacuum impregnation method in step (3) is as follows: first, the pretreated high water absorption aggregate is vacuumed, and then the high water absorption aggregate is impregnated under pressure so that the penetrating material can fully penetrate into the internal pores of the aggregate; the vacuum degree of the vacuum pressure impregnation method is -0.06~-0.09MPa, the pressure is 0.3~0.8MPa, and the impregnation time is 30~90min.

8. The method for modifying high water absorption aggregate according to claim 6, characterized in that, In step (3), the impregnation material is stirred every 15 to 20 minutes during the vacuum pressure impregnation process, with a stirring speed of 60 to 300 r / min and a stirring time of 2 to 3 minutes.

9. The method for modifying high water absorption aggregate according to claim 1, characterized in that, The hollow PVA fiber tube mentioned in step (4) has a diameter of 0.05~0.2mm and a length of 2~5mm; and the diameter of the hollow PVA fiber tube is not greater than 2 / 3 of the surface aperture D50 of the aggregate.

10. The method for modifying high water absorption aggregate according to claim 1, characterized in that, In step (4), the mass percentage of the magnetic nanoparticles in the magnetic fluid is 5% to 10%, and the particle size of the magnetic nanoparticles is 5 to 20 nm.

11. The method for modifying high water absorption aggregate according to claim 1, characterized in that, In steps (4) and (5), the alkaline dispersion is prepared by sodium hydroxide and deionized water, with a pH value of 13-14.